2017
DOI: 10.4018/ijthi.2017010103
|View full text |Cite
|
Sign up to set email alerts
|

User-Friendly Security Patterns for Designing Social Network Websites

Abstract: The number of users in Social Networking Sites (SNSs) is increasing exponentially. As a result, several security and privacy problems in SNSs have appeared. Part of these problems is caused by insecure Graphical User Interfaces (GUIs). Therefore, the developers of SNSs should take into account the balance between security and usability aspects during the development process. This paper proposes a set of user-friendly security patterns to help SNS developers to design interactive environments which protect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Acknowledging the challenges of community management, namely protecting user privacy while being user-friendly (Alemerien, 2017), the notion of trust is paramount. We observed that the tour operator plays a key role in co-creating the ski-chalet experience by bringing the group together and enabling the experience (Morgan and Xu, 2009;Prahalad & Ramaswamy, 2004) which tourists later share via social media (Munar & Jacobsen, 2014).…”
Section: Augmented Communities Of Online and Offline Skiersmentioning
confidence: 99%
“…Acknowledging the challenges of community management, namely protecting user privacy while being user-friendly (Alemerien, 2017), the notion of trust is paramount. We observed that the tour operator plays a key role in co-creating the ski-chalet experience by bringing the group together and enabling the experience (Morgan and Xu, 2009;Prahalad & Ramaswamy, 2004) which tourists later share via social media (Munar & Jacobsen, 2014).…”
Section: Augmented Communities Of Online and Offline Skiersmentioning
confidence: 99%
“…In another article, the authors explored the role of GUIs in managing security and privacy settings in social networks [47]. The authors describe a series of security models to assist SNS developers in designing interactive environments that protect individuals' privacy and security while being extremely user-friendly.…”
Section: Helping Security Developers Improve Usability (7 Papers)mentioning
confidence: 99%
“…In some studies, the recommendations resemble reflections on "organizational" aspects, such as (1) the need to assign specific responsibilities to each stakeholder to increase their motivation and prevent the diffusion of responsibilities; (2) understanding the motivations behind the need for security; (3) the security design process should involve, be inclusive, and understandable for all participants; (4) identifying security anecdotes and scenarios [42]. In other studies, the recommendations are very general, focusing on ease of use rather than usability [44], urging developers to concentrate on integrating graphical user interfaces (GUIs) with security aspects to create a user-friendly GUI [43,47]. However, what it means to simplify the design to make GUIs more user-friendly remains unclear.…”
Section: Helping Security Developers Improve Usability (7 Papers)mentioning
confidence: 99%